Disused areas and urban regeneration. The historic centre of Vicenza, Italy - Pietrogrande, Enrico; Dalla Caneva, Alessandro; Navàs Salvadó, Ignasi (Journal of Architecture and Urbanism, 2017)
This work concerns Vicenza, a city located not far from Venice in the north-east corner of Italy, and it specifically refers to an area situated on the outskirts of the city’s urban fabric between the perimeter of its ancient walls and the banks of the Bacchiglione river, in the shadow of the abandoned monastery of St. Biagio.The idea of restoring that physically and socially degraded area of the city of Vicenza has long been the object of discussion on the part of local authorities. Once intimately linked to the city’s historic center, the area gradually lost its functional and social identity becoming first a parking lot and then equipped as a city warehouse.The intent to regenerate the area and the observation that the relationship between the city and its river is constantly refused, or delayed, lead to recognize in the long edge of the area a unique meeting opportunity which allows to repair the water-city association, recuperating rituals and connections from the past. The municipality is presently planning on pursuing a qualitative restoration of the area which will be used for social and cultural enrichment.The final part of the current work outlines some proposals that were developed during the Architectural and Urban Composition 2 course recently offered by the Department of Civil, Environmental and Architectural Engineering of the University of Padua (Italy).